An Information Interpretation of Financial Analyst Superiority in Forecasting Earnings - Brown, Lawrence D.; Richardson, Gordon D.; Schwager, Steven J. (Journal of Accounting Research, 1987)
Lawrence D. Brown, Gordon D. Richardson, Steven J. Schwager, An Information Interpretation of Financial Analyst Superiority in Forecasting Earnings, Journal of Accounting Research, Vol. 25, No. 1 (Spring, 1987), pp. 49-67